Recent advances in studies of news consumption - Francesco Capozza; Ingar Haaland; Christopher Roth; Johannes Wohlfart (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
We review recent advances in the literature on news consumption. We first provide an overview of different empirical techniques to measure news consumption, including browser data, TV viewership data, and survey-based measures. We also discuss the pros and cons of these different techniques. We next examine ways of differentiating between different theories of news consumption, such as preferences for accuracy versus belief confirmation motives. We conclude by highlighting possible directions for future research.
Keywords: C90; D83; D91; 330; News Consumption; Information Demand; Click Data; Surveys